Maximizing operating room efficiency by effectively managing elective case cancellation. Issue 1 (January 2019) - Hadeed, Michael M.; Patel, Vandan D.; Novicoff, Wendy M.; Gwathmey, Frank Winston
Abstract : Background: Surgery cancellation and rescheduling affect efficiency and satisfaction, both critical aspects of the modern orthopaedic practice. The purpose of this study was to critically and comprehensively evaluate cancellations to define actionable ways to improve efficiency, with the goal to develop evidence-based, transparent rescheduling policies. Methods: A retrospective review was completed of all patients who were scheduled for elective surgery over 1 yr. Outcome measures included rate of cancellation, interval from time of cancellation to scheduled surgery date, risk factors for cancellation, re-schedule rate, re-cancellation rate, and risk factors for re-cancellation. Results: There were 7, 215 elective surgeries, 13% of which were cancelled prior to surgery. Forty-four percent of surgeries were cancelled within 3 days of the surgery. Of those that were cancelled, 53% were rescheduled, 21% of which had cancelled again, which was significantly higher than the comparison group of first-time cancellations. Those that were cancelled without a correctable reason had significantly more re-cancellations and a lower procedure completion rate. Conclusions: When scheduling surgeries, it is more efficient to preference surgeries that have not been previously cancelled, and among previously cancelled surgeries to preference those with a correctable reason for cancellation. While not novel concepts, this study provides an evidence base for rescheduling policies, which can be made transparent for patients. Ultimately, this may improve efficiency as well as patient trust and satisfaction.